Optimisation of research laboratory, space utilisation and inventory control and storage - Wee, Kia Min (2019)
Inventory management has been a very important part of most industry, it is the most important tool to improve operational efficiency and in reducing relevant inventory cost. Space management also helps to effectively manage the space to reduce the cost of wasted space. The importance of inventory cost should not be taken lightly. Studies have shown that the expenses related to space have been the second highest in a higher education institution. Now that the studies show the space management for institute of higher education are very important, therefore, space and facilities management must be the main agenda and need to be managed efficiently and appreciated wisely. Poor housekeeping would lead to space not being fully utilised and poor inventory management. This has been a huge problem in most of the laboratory in NTU. Therefore, the aim of this report is to document the methods used to utilise space and the development of a software in order to track the inventory on the Biological laboratory in NTU. In Phase 1 of this project, the optimisation of spaces for storage of consumables was performed. Drafting of the layout and collection of relevant data for better visuals of the existing layout has been done. The 5S approach is then performed on the existing layout to maximise the space available. proposed layout is then compared to the existing layout to identify if the workflow and storage spaces have been maximised. In Phase 2 of this project, an inventory management software has been developed using Excel VBA programming. The purpose of this software is to track all the stocks input and output. With the implementation of this software, it should improve the traceability and reduce discrepancies whenever inventory is drawn or received. Max/Min method will also be implemented for the administrator to identify when to reorder, this will be able to prevent over-purchasing of inventories which would cause a lack of storage space. By implementing both phases, the laboratory will be able to be kept in order, preventing over-purchasing, which will cause the hazardous level to increase. Thus, implementing both phases will prevent the laboratory from reverting back to its old practices.